INDUSTRI KREATIF “TENUN MUNA” DAN PEMASARAN ONLINE (studi deskriptif dinamika pemasaran hasil tenun daerah Kabupaten Muna Sulawesi Tenggara) - Wa Ode Lusianai; La Tarifu; Ikrima Nurfikria; Aryuni Salpiana Jabar (Universitas Serang Raya, 2019)
Weave is the identity and wealth inherent in a region. In Muna district, it is also known tohave high quality weave with diverse and interesting motifs. However the fundamental problem amongweavers is the limited media or means of promotion and sale of their weaving products. The lack ofknowledge and skills in utilizing the information technology; also the fear of weavers on motifs